Autoimmune pulmonary alveolar proteinosis prior to myelodysplastic syndrome. Issue 5 (5th May 2020) - Foo, Chuan Tai; Chhor, Louis; Thien, Francis
Abstract: We report the first case of autoimmune pulmonary alveolar proteinosis (PAP) associated with and preceding myelodysplastic syndrome. A 74‐year‐old female with a history of polymyalgia rheumatica presented with six months history of progressive exertional breathlessness. Examination revealed bilateral chest crackles and exertional desaturation. A diagnosis of autoimmune PAP was made based on the presence of autoantibodies to granulocyte‐macrophage colony‐stimulating factor and characteristic findings on chest computed tomography, bronchoalveolar lavage, and transbronchial biopsies. Bilateral whole lung lavage was performed with prompt improvement in symptoms. Fourteen months later, she presented with new breathlessness and was diagnosed with myelodysplasia on bone marrow biopsy. No recurrence of alveolar proteinosis was detected. This case highlights the importance of follow‐up and screening of patients with autoimmune PAP for haematological conditions. Abstract : We report the first case of autoimmune pulmonary alveolar proteinosis associated with and preceding myelodysplastic syndrome.